2019
DOI: 10.3390/jcm8122210
|View full text |Cite
|
Sign up to set email alerts
|

Erastin Inhibits Septic Shock and Inflammatory Gene Expression via Suppression of the NF-κB Pathway

Abstract: Sepsis is a life-threatening condition that is caused by an abnormal immune response to infection and can lead to tissue damage, organ failure, and death. Erastin is a small molecule capable of initiating ferroptotic cell death in cancer cells. However, the function of erastin in the inflammatory response during sepsis remains unknown. Here, we showed that erastin ameliorates septic shock induced by cecal ligation and puncture or lipopolysaccharides (LPS) in mice, which was associated with a reduced production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
2
25
1
Order By: Relevance
“…Next, HEK-293 cells were cultivated with a Cy3-conjugated secondary antibody for 1 h. Finally, cells were cultivated with DAPI for 5 min. Pink fluorescence (red and blue images overlaid) indicated nuclear translocation of NF-κB p65 protein, and could be observed simultaneously by a confocal laser scanning microscope (Zeiss, Wetzlar, Germany) at an excitation wavelength of 350 nm and 540 nm for DAPI and Cy3 ( Oh et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, HEK-293 cells were cultivated with a Cy3-conjugated secondary antibody for 1 h. Finally, cells were cultivated with DAPI for 5 min. Pink fluorescence (red and blue images overlaid) indicated nuclear translocation of NF-κB p65 protein, and could be observed simultaneously by a confocal laser scanning microscope (Zeiss, Wetzlar, Germany) at an excitation wavelength of 350 nm and 540 nm for DAPI and Cy3 ( Oh et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Toll-like receptor 4- (TLR4-) nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) signaling pathway activates the expression of several proinflammatory cytokine genes that play pivotal roles in inflammatory disorders, such as sepsis, ulcerative colitis, myocardial infarction, and I/R injury [ 78 80 ]. The pretreatment of bone marrow-derived macrophages (BMDMs) with the ferroptosis inducer erastin significantly attenuates the expression of proinflammatory cytokines (e.g., inducible nitric oxide synthase, tumor necrosis factor- (TNF-) α , and interleukin- (IL-) 1 β ) induced by lipopolysaccharide (LPS) treatment, and these effects are mediated by inhibition of the phosphorylation of I κ B kinase β (IKK β ) and the phosphorylation and degradation of I κ B α and NF- κ B and thereby lead to the suppression of sepsis development [ 80 ]. Ferroptosis is detected in intestinal epithelial cells from patients with ulcerative colitis and mice with colitis, and Fer-1 alleviates experimental colitis [ 79 ].…”
Section: Posttranslational Modifications (Ptms) In Ferroptosismentioning
confidence: 99%
“… Li et al (2018) demonstrated that Gpx4 activator can suppress inflammatory conditions through the inhibition of the NF-κB pathway. And other researchers also discovered that erastin had similar roles in inflammatory response by suppressing the NF-κB signaling pathway, resulting in inhibition of sepsis development ( Oh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%